Study guides

Q: What is B plus B plus B plus C plus C plus C?

Write your answer...

Submit

Related questions

b + b + b + c + c + c + c = 3b + 4c

b+b+b+c+c+c+c =3b+4c

It is the same as: 3b+4c which is an algebraic expression

2b+3c

2b + 2c or 2(b + c)

a= (+a) or a= (-) b= 2a b= 2a c= (-a) c= (+a)

And how does this relate to coins?

Because there is no way to define the divisors, the equations cannot be evaluated.

A+c= 2a+b

the answer is a

a=24 b=16 c=18

It is 10b + 2c

yes

C & D are the products Apex

If a + b + c + d + 80 + 90 = 100, then a + b + c + d = -70.

C equals A plus B under all circumstances; C= A + B.

If: a = b+c+d Then: c = a-b-d

x + y + z = 0 x = a - b, y = b - c, z = c - a, therefore a - b + b - c + c - a = ? a - a + b - b + c - c = 0

A B plus C plus D plus E plusorA B C D E plus plus plus plusor variations.

It is a*a + b*b + c*c

b+c^2 There is no way to simplify that.

2a + 2b = 26 2b + c = 22 ===> b = 11 - c/2 4c + 2b = 46 ===> b = 23 - 2c From the 2nd and 3rd equations: 11 - c/2 = 23 - 2c 22 - c = 46 - 4c 22 - 46 = -4c + c ===> -24 = -3c ===> c = 8 Substitute c=8 into the 3rd equation: b = 23 - 16 = 7 Substitute b=7 into the 1st equation: 2a + 14 = 26 2a = 12 ===> a = 6

Ax + B = Bx + C Ax - Bx = (C - B) x (A - B) = (C - B) x = (C - B) / (A - B)

(a+b+c) (a+b-c)

That depends on the value of the variables (A, B, and C). It can be anything.